Menghidupkan kembali permainan dam-daman sebagai sarana dan motivasi belajar yang menyenangkan di sekolah dasar - Fu’adi, Eka Agustin; Ainin, Aiska Hidayatul; Fauziah, Cindy Amilatul (Maliki Interdisciplinary Journal, 2025)
Dam-Daman, as a part of Indonesia’s local cultural heritage, holds significant educational value that can be utilized within the realm of education, particularly at the elementary school level. This article explores how the game serves not only as entertainment but also as an effective and enjoyable learning medium. Through thematic approaches, discovery learning, and problem-based learning, Dam-Daman has been proven to enhance learning motivation, critical thinking skills, and students’ social abilities. Moreover, the game helps preserve cultural heritage while instilling character values such as sportsmanship, cooperation, and patience. The implementation and evaluation results show that Dam-Daman has great potential to be adopted as a contextual learning model amid the challenges of modern education. Furthermore, the integration of the traditional game of Dam-Daman into the elementary school curriculum provides a learning alternative that adapts to the needs of students in the digital age, while remaining rooted in local culture. This research finding confirms that the collaboration between modern learning methods and local wisdom can create a more humanistic, enjoyable, and meaningful learning environment. Therefore, the Dam-Daman game can be used as an innovative strategy to enrich character- and culture-based learning models, while simultaneously strengthening national identity through education.